Soft-tissues stabilization after immediate implant; platform switch with supraperiosteal augmentation - Farhan Durrani (Wolters Kluwer Medknow Publications, 2021)
The architecture around an oral implant pushes the clinicians for an equalization of biological and physiological requirements. An esthetic implant-supported restoration needs plethora of knowledge and expertise. Surgeon skills can be of use for correct tridimensional position of implant in the extraction socket, shaped abutment contours, and anatomical final crown. An immediate implant placement for a fresh socket requires existing oral parameters judgment and evidence-based treatment plan. They are hard- and soft-tissue relationship, gingival biotype, and the tooth position. In this article, we describe a case of immediate implant placement, provisional crown, bovine bone contraction, soft-tissue collapse, and its management.